A randomized controlled trial to evaluate the efficacy of metacognitive training for people with schizophrenia applied by mental health nurses: Study protocol - Pinho, Lara Manuela Guedes (2020)
Submitted by zulmira ribeiro (zulmira@esenf.pt) on 2020-12-28T11:19:03Z No. of bitstreams: 1 artigo afiliado Csequeira-03.pdf: 445012 bytes, checksum: 540304cc7730655fbc52a9986d120306 (MD5)